Cellulolytic activities of a novel Fomitopsis sp. and Aspergillus tubingensis isolated from Philippine mangroves - Bacal, Christine Jurene O.; Yu, Eizadora T. (2017)
The ability to deconstruct plant cell wall polysaccharides is inherent in fungal endophytes. As such, discovering organisms that secrete potent cocktails of carbohydrate-active enzymes may hold the key to deconstructing waste agricultural biomass for industrial applications. Based on CMC-Congo red plate based assay, two fungal isolates derived from mangrove trees (JB10 and JB11) showed high enzymatic indices (as high as 5.6 ± 0.18 for JB10). Both isolates were then grown in potato dextrose (PD), carboxymethylcellulose(CMC), and beechwood xylan (XY), and the corresponding endoglucanase, xylanase, and β-glucosidase activities of the enzymes present in crude culture supernatants were determined. JB11 showed significant increase in endoglucanase activity (0.36 ± 0.04 U/mL) in PD, while JB10 endoglucanase activity was similar between the three media. Interestingly, xylanase activity of both isolates was relatively high (ranging 0.26-1.0 U/mL), with JB10 xylanase activity five-fold higher in PD. Lastly, there was 2-4 fold increase detected in β-glucosidase activities (0.59-0.8 U/mL) in both isolates when grown in CMC or XY media. Phylogenetic analysis of the ITS sequences show that JB11 is Aspergillus tubingensis, while JB10 is a novel Fomitopsis sp. isolate. (Author's abstract)